The teachers' personal characteristics and feedback on task performance the effects on student evaluation of teacher's instructional skills. - Distura, Eideleen Grace P.
This study investigated the effects of teacher's personal characteristics and feedback on task performance to the evaluation of teacher's instructional skills by sixty first year students from the Division of Social Sciences. Using the analysis of variance, the teacher's personal characteristics had no significant effect on student evaluation of teacher's instructional skills. Findings also reveal that feedback on task performance negatively affects student evaluation of teacher's instructional skills. No statistically significant interaction effects were found between teacher's personal characteristics and feedback on task performance. Personal characteristics and feedback on task performance, whether positive or negative did not show significant differences when students evaluations were assessed.